Beyond classical liberalism: Freedom and the good - Rooney, James Dominic; Zoll, Patrick, 1977- (Abingdon, Oxon ; New York, USA: Routledge, 2024)
"This volume brings together diverse sets of standpoints on liberalism in an era of growing skepticism and distrust regarding liberal institutions. The essays in the volume: - Relate concerns for liberal institutions with classical themes in perfectionist politics, such as the priority of the common good in decision-making or the role of comprehensive doctrines. - Analyse how perfectionist intuitions about the political life affect our concepts of public reason or public justification. - Outline various moral duties we have toward other persons that underlie the liberal institutions or notions of rights functioning across the contemporary political landscape. - Explore various aspects of pluralism from within influential religious or philosophical traditions, applying insights from those traditions to issues in contemporary politics. The comprehensive volume will be of great interest to scholars, students, and researchers of politics, especially those in political philosophy and political theory"--
Introduction / James Dominic Rooney & Patrick Zoll -- Republican freedom, social justice, and democracy / Philip Pettit -- Political perfectionism and spheres of state neutrality / Steven Wall -- The common good of nations and international order / Mark Retter -- Contractual obligation and the good : beyond classical liberalism / Stephen Hall -- Discursive equality and public reason / Thomas M. Besch -- Perfectionist public reason liberalism : why public reason liberalism should be reconcilable with political perfectionism / Patrick Zoll -- Liberal arts and the failures of liberalism / James Dominic Rooney -- Perfectionism, political justification, and Confucianism / Fan-lun Franz Mang -- Religion, democratic deliberation, and the requirement of fallibilism / Paul Billingham -- Perfectionism and respect of persons / Natalie Stoljar -- Tolerance as turnabout : fair play, freedom, and republican character / Andrew Murphy -- Human rights in the natural law tradition / Jonathan Crowe -- Well-being policy : consensus hallmarks and cultural variation / Dan Haybron -- Aristotle, Athens, and modern democracy : prospects for a usable past / V. Bradley Lewis -- Liberty and the good in the American founding / Vincent Phillip Muñoz -- Confucian perfectionism and resources for liberties / May Sim.
Includes bibliographical references and index.
Keywords: Liberalism -- Philosophy; Political Science; Liberty -- Philosophy; Common good -- Philosophy; Perfection